Integration of Bumdes to Encourage Village Community Economic Activities - Istiqaroh, Choirum Rindah; Warnaningtyas, Hartirini; Indartini, Mintarti; Wihara, Dhiyan Septa (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: The establishment of Village-Owned Enterprises (BUMDes) aims to stimulate economic growth in rural areas. Each BUMDes is expected to align with the community's needs, particularly in supporting local economic activities. As a result, BUMDes should be viewed not as competitors by local businesses, but as partners that strengthen the village economy. This research aims to compare the economic conditions of the village community before and after the establishment of BUMDes Wonosegoro, focusing on the positive impacts and significant changes that occurred. Design/methodology/approach: This study uses a quantitative approach with Paired Sample t-test analysis to measure significant changes in community economic activities before and after the presence of BUMDes. The respondents in this study consisted of 30 residents of Cermo Village, Kare Sub-district, Madiun Regency, who were randomly selected to ensure good representation of the village population. Findings: The results of this study show that there are significant differences in several economic variables after the establishment of BUMDes Wonosegoro. Specifically, there was an increase in variables X4 and X5, indicating that BUMDes has successfully increased income and economic activities in the village. However, other variables did not show significant changes, suggesting that the impact of BUMDes may take longer to materialize across all aspects of the village economy. Research limitations/implications: This research focuses only on one BUMDes in Cermo Village. Therefore, the results may not be fully generalizable to BUMDes in other areas. Further research comparing multiple BUMDes in different villages is needed to provide a broader picture and enrich the findings of this study. Practical implications: The results of this study can be used as evaluation material for BUMDes Wonosegoro managers to improve synergy with the needs of village communities. By optimizing the role of BUMDes, it is expected that community welfare will be enhanced through local job creation and sustainable economic empowerment. Originality/value: This research offers an original comparative analysis of the impact of BUMDes on village economic activities using quantitative statistical methods. This study contributes to the literature on the role of BUMDes in rural economic development, especially in the context of Indonesian villages. Paper type: Research paper